Application of Dominant Movement Patterns in Front Roll Learning - Diky Hadyansah; Wiguna, Mugi; Budiman, Ali (STKIP Paasundan Press, 2024)
The low skills of students in learning front roll floor gymnastics in class VI SDN Jaya Mekar are the focus of this research problem. This study aims to determine the effect of the dominant motion pattern approach on front roll floor exercise skills. The method used is experimental research design one group pretest posttest design. The population and sample of this study were all VI grade students of SDN JAYA MEKAR as many as 32 students, sampling using total sampling with a sample of 32 students. The instrument used in this study was a front roll skill test. Data analysis techniques using paired sample t-test. The results showed t-count 48.481> t-table 2.039 which shows the dominant motion pattern approach has an effect on the front roll floor gymnastics skills of classVI SDN JAYA MEKAR students.